PENGARUH IKLAN, PROMO GRATIS ONGKIR, DAN FLASH SALE TERHADAP KEPUTUSAN PEMBELIAN PADA BLIBLI DI KEBUMEN - Rafianti, Widya Aulia; Rokhmat (Jurnal EMT KITA, 2024)
This study aims to examine the effect of advertisements, free shipping promos, and flash sales on purchasing decisions at Blibli in Kebumen. The population in this study were Blibli users who had made at least one purchase transaction or prospective buyers who knew Blibli. The sample size was 100 respondents. Data collection techniques were conducted using questionnaires. The data analysis used included instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient tests. Data processing was carried out using SPSS version 25.0. The results showed that: (1) Advertising has no partial and significant effect on purchasing decisions on Blibli in Kebumen. (2) Free shipping promos have a partial and significant effect on purchasing decisions at Blibli in Kebumen. (3) Flash sales have a partial and significant effect on purchasing decisions at Blibli in Kebumen. (4) Advertising, free shipping promos, and flash sales have a simultaneous and significant effect on purchasing decisions at Blibli in Kebumen.